2009
DOI: 10.1007/s12550-009-0038-7
|View full text |Cite
|
Sign up to set email alerts
|

Complex etiology and pathology of mycotoxic nephropathy in South African pigs

Abstract: Spontaneous nephropathy in pigs seen in South Africa was found to have multi-mycotoxic etiology involving several mycotoxins such as ochratoxin A (OTA), penicillic acid (PA) and fumonisin B1 (FB1) in addition to a not yet identified mycotoxin. Contamination levels of OTA were comparatively low (67-75 μg/kg) in contrast to high contamination levels of FB1 (5,289-5,021 μg/kg) and PA (149-251 μg/kg). A heavy contamination with Gibberella fujikuroi var. moniliformis and Penicillium aurantiogriseum complex (mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 63 publications
4
64
1
Order By: Relevance
“…It has been observed, for example, that the simultaneous presence of OTA and fumonisins in feeds intended for pigs favors a "multi-toxicological" effect, with sero-hemorrhagic as cites and pulmonary hemorrhages and hydrothorax among the principal symptoms (Stoev et al, 2010). Moreover, synergistic effects on both liver and kidneys were observed after the ingestion of feed by rabbits contaminatedwithAFB 1 and FB 1 (Orsi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed, for example, that the simultaneous presence of OTA and fumonisins in feeds intended for pigs favors a "multi-toxicological" effect, with sero-hemorrhagic as cites and pulmonary hemorrhages and hydrothorax among the principal symptoms (Stoev et al, 2010). Moreover, synergistic effects on both liver and kidneys were observed after the ingestion of feed by rabbits contaminatedwithAFB 1 and FB 1 (Orsi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…polonicum has been recently indicated as a fungus involved in the porcine nephropathy in Bulgaria and South Africa (Stoev et al 2010aStoev et al 2010b, and it has been also identified in poultry mixed feeds in Slovakia (Labuda and Tančinová 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These specific adducts are found in human urothelial tumours in EN regions [8,60]. The possible multi-toxin aetiology of EN and porcine nephropathy in Bulgaria and South Africa are supported by experiments from Stoev et al [12,101,122] on pigs: the combination of OTA and FB 1 caused stronger lesions in the kidneys, more pronounced changes in biochemical parameters, and disturbances in the humeral immune response in doses that correspond to those found in cases of porcine nephropathy in Bulgaria and South Africa.…”
Section: Toxicity Of Mycotoxin Combinations Involving Otamentioning
confidence: 93%